INDUSTRIALISASI GULA DI JAWA TIMUR : PABRIK GULA MERITJAN KEDIRI 1883-1929 - Sakafitri Rimasari (Historiography: Journal of Indonesian History and Education, 2021)
During the colonial period of the Dutch East Indies, sugar was an important commodity in the international market besides spices,tea, and coffee. The demand for sugar is increasing along with its development. Seeing the urgency of the sugar commodity, sugar factories were finally established, including the Meritjan Sugar Factory (Suikerfabriek Meritjan) which is located in Kediri, East Java. The practice of the sugar industry at the Meritjan Sugar Factory was studied using quantitative methods and literature studies were carried out to obtain appropriate data to achieve the objectives of the discussion. Where the purpose of conducting a discussion on the sugar industry in East Java, precisely at the Meritjan Sugar Factory, is to study the sugar factory industry and its impact on the socio-economic life of the community. In this study, it can be seen that sugar factories and sugarcane plantations are interrelated and have an important role in the socio-economic life of the community at that time.Pada masa kolonial Hindia Belanda, gula merupakan komoditas yang penting dalam pasar internasional selain rempah-rempah, teh, dan kopi. Permintaan akan gula semakin meningkat seiring perkembangannya. Melihat urgensi komoditas gula tersebut akhirnya didirikanlah pabrik-pabrik gula, diantaranya adalah Pabrik Gula Meritjan (Suikerfabriek Meritjan) yang terletak di Kediri, Jawa Timur. Praktik industri gula di Pabrik Gula Meritjan ini dikaji dengan metode kualitatif serta dilakukan studi kepustakaan untuk memperoleh data-data yang sesuai untuk mencapai tujuan dari pembahasan. Dimana tujuan dilakukannya pembahasan mengenai industri gula di Jawa Timur tepatnya di Pabrik Gula Meritjan ini adalah mengkaji industri pabrik gula dan pengaruhnya pada kehidupan sosial ekonomi masyarakat. Dalam kajian ini dapat dilihat bahwa pabrik gula serta perkebunan tebu saling berkaitan dan memiliki peran penting dalam kehidupan sosial ekonomi masyarakat pada masa tersebut.